Decolonising Sambo : transculturation, fungibility and black and people of colour futurity - Tate, Shirley Anne (Critical mixed race studies., 2024)
sambo is racialised naming, deeply rooted in the colonial legacies of white European settler colonial societies globally, including Australia, the Caribbean, South Africa, the USA, Canada and Latin America. This second edition of Decolonising Sambo: Transculturation, Fungibility and Black and People of Colour Futurity develops further the Black decolonial feminist theoretical framing of sambo as a white settler colonial psyche artefact by incorporating 'whiteness as property' into the critical theories used to analyse its construction. Tate examines manifestations of sambo in different contexts, including Canada's Prairies, while shedding light on the persistence of racist caricature across the Americas, Europe and beyond. The work offers an analysis of Indigenous Australians' experiences within the framework of global Black liberation thought and continuing dispossession. It also discusses the ongoing Caribbean Reparations movement. Throughout, the text underscores the enduring significance of sambo as colonial psychic remainder amidst broader discussions on global anti-Blackness, particularly in the aftermath of the #BLM movement. Drawing from historical, cultural and socio-political perspectives, this new edition provides scholars and students with insights into anti-Black racial formations, colonial power structures and critical theories, enriching discussions on race, identity and decolonisation across academic disciplines.